PEMBUATAN ALAT KOMPOSTER DAN TAKAKURA UNTUK MENGOLAH SAMPAH ORGANIK: Metode Pengelolaan Sampah Organik - Seme, Alan Kristian; Antoh, Alfius Benyamin; Marasabessy, Dzulfikar; Way, Jhose Rizal; Kumune, Roberth Richardo (LRI Universitas Muhammadiyah Sorong, 2025)
Organic waste management is one of the environmental challenges that requires practical and environmentally friendly solutions. This study aims to design and create organic waste management tools in the form of a composter and Takakura using experimental methods. The composter is designed to support the aerobic composting process with air ventilation, while the Takakura is equipped with coconut fiber pads and cardboard protectors to maintain humidity and air circulation. The manufacturing process is carried out using simple materials and easily accessible equipment, making both tools practical for application on a household scale. The test results show that both tools are effective in processing organic waste into nutrient-rich, environmentally friendly compost that has the potential to support sustainable agriculture. This study concludes that the use of composters and Takakura can be an effective solution to reduce the volume of organic waste that ends up in landfills (TPA), while increasing public awareness of the importance of sustainable waste management. This tool is expected to encourage better waste management and contribute to the creation of a clean and healthy environment.